1988
DOI: 10.1002/ajmg.1320290138
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the gene for X‐linked nephrogenic diabetes insipidus to Xq28

Abstract: X-linked nephrogenic diabetes insipidus (NDI) was segregating in a large Indiana family. It was tested for linkage of the NDI gene to X-chromosome molecular markers. Maximum lod scores of 3.15 and 3.01 (theta = 0) obtained for the molecular markers F8A (F8C) and DXS15 (DX13) respectively, indicate that the NDI gene is located in Xq28. A lod score of 3.61 (theta = 0) was obtained with multipoint linkage analysis of F8A and DXS15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 11 publications
(3 reference statements)
1
9
0
Order By: Relevance
“…In the three additional small families analyzed, the exact inheritance pattern could not be categorically ascertained, but these patterns are consistent with an X chromosome-linked recessive form, the most common inheritance form in NDI (1). Multipoint linkage analysis data in our large family suggest linkage of the disease with DXS52 and F8C, both markers on the distal end ofthe X-chromosome (7,8,24,25). Furthermore, data by Bichet et al (34) confirmed the locus homogeneity in 13 independent families with X chromosome-linked recessive NDI.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In the three additional small families analyzed, the exact inheritance pattern could not be categorically ascertained, but these patterns are consistent with an X chromosome-linked recessive form, the most common inheritance form in NDI (1). Multipoint linkage analysis data in our large family suggest linkage of the disease with DXS52 and F8C, both markers on the distal end ofthe X-chromosome (7,8,24,25). Furthermore, data by Bichet et al (34) confirmed the locus homogeneity in 13 independent families with X chromosome-linked recessive NDI.…”
supporting
confidence: 74%
“…In most families thus far reported, the mode of inheritance follows an X chromosome-linked recessive pattern with variable expression in female carriers (3,4), although autosomal dominant (5) and autosomal recessive (6) modes of inheritance have also been described. Linkage analyses offamilies with the X chromosome-linked recessive form of NDI documented tight linkage of the disease-related gene to a number of markers in the subtelomeric region ofthe long arm ofX chromosome (Xq28) (7,8), the region where the vasopressin type 2 receptor (V2R) also maps (9,10). Under normal conditions, AVP (or its analogues) bind to a specific renal tubular receptor, the V2R that is coupled to adenylyl cyclase via a GTP-binding protein (G protein).…”
mentioning
confidence: 99%
“…AVPR2 is encoded by a single gene that has been mapped to chromosome Xq28 (Kambouris et al 1988; Van den Ouweland et al 1992). The gene comprises three exons, spanning approximately 2 kb .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it is characterized by hyposmotic polyuria despite high plas ma concentrations of vasopressin. The action of vasopres sin is mediated by 2 sets of receptors, V 1 and V2; the lat ter is responsible for the antidiuretic effect [1], In most affected families, NDI is transmitted as an X-linked recessive disorder [2], Linkage studies have located the responsible gene on the long arm of the X chromosome in region 28 (Xq28) [3][4][5]. The gene for the vasopressin V2 receptor (AVPR2 gene) was cloned and also localized to Xq28 [6,7], strongly suggesting that the receptor may be the site of the defect in NDI.…”
Section: Introductionmentioning
confidence: 99%